The Rikord Submarine Volcanic Massif, Kuril Island Arc - Blokh Yu. I.; Bondarenko V. I.; Dolgal’ A. S.; Novikova P. N.; Petrova V. V.; Pilipenko O. V.; Rashidov V. A.; Trusov A. A. (My University, 2018)
This paper reports a study of the Rikord volcanic massif. The massif consists of four volcanic edifices that coalesce in their bases, and is most likely Quaternary. The massif discharged basaltic and basaltic andesite lavas during its earlier life. The observed high natural remanent magnetization that was found in dredged rocks is due to high concentrations of single-domain and pseudo-single-domain grains of titanomagnetite and magnetite. We have identified the directions of the conduits and the presence of peripheral magma chambers. A 3D model has been developed for the central part of the Rikord volcanic massif; the model includes ten large disturbing magnetic blocks that are most likely cooled, nearly vertical, conduits.
Keywords: 38.37.25 Вулканология; 38.37.27 Петрография океанических пород и подводный вулканизм; Рикорда